Dinamika Kampanye Politik Dalam Demokrasi Elektoral (Studi Deskriptif - Analitis Kampanye Pemilukada Serentak 2018 di Propinsi Jawa Tengah) - Yuliyanto, Muchamad (Master of Communication Science Program, Universitas Diponegoro, 2018)
Political campaigne is tools to persuad constituen in the general election, because campaigne is the part of political activity in practical of democracy. In the political campaigne so politician sends ideas, mission and planning program that is realized when he lead in government. In facts, campaigne needs the medium help sending programmes and ideas to public. In general election of governour in central of Java so there are any kinds of campaigne in general election; (1) direct campaigne who politician constructs direct communication with constituen, example; public communication in the room, dialog to public. (2) campaigne by mainstream media, when politician sends ideas and missin via mainstream media: newspaper, radio, TV and outdoor media as advertising by baliho, calender, or videotron in public spaces. (3) campaigne using social media, since 2014 until now many politician used its to construct political communication, because in the social media participants can dialog to discuss about ideas and programme from politician. Besides that, in political campaigne there are determinant factor of success to influence constituen who that contents of political messages send to constituen. Whe contents from political messages in campaigne give to public expectation with logic and realistic so politician get easily public supporting that to oriented personal choice in general election.